The mechanical properties of fly ash concrete prepared and cured at high temperatures - D.R. Munaf; M.S. Besari; M.M. IqbaP;; I. Kadir (Universitas Gadjah Mada, 2001)
Results of an experimental investigation on the effect of fly ash content, water cement (w/c) ratio of concrete prepared and cured at temperatures of ambience, 40°C and 60°C are presented in this paper. The mechanical properties investigated here include its workability, its behaviour under compression and splitting tension. Microscopic investigations were also carried out using SEM micrographic images to gain understanding of concrete at its microstructural level.The results indicate that high temperature increases early compressive strengths of concrete, but has decreasing effects on the strengths at later ages. The use of fly ash in concretes cast and cured at elevated temperatures improves the physical and mechanical properties of fresh as well as those of hardened concrete.Various mathematical models describing the properties of such concretes are considered at the end of this paper. The strength properties of high temperature fly ash concrete were best represented by a simple exponential function of time, while its stress-strain relationship could be best described by an exponential function of strain of a more complicated form.